Determination of friction angle of soil using double-punch test approach: An experimental study. Issue 1 (1st January 2017) - Hasan, Mohammad Mehedi; Rashid, Md. Abdur
Abstract: Estimation of soil strength indices is prerequisite for the design of foundations, pavements, retaining walls and many other engineering interventions. Friction angle, φ is a shear strength parameter which is very crucial in assessing the stability of slopes and soil. There are a variety of options computing friction angle of soil. This paper rendered the experimental study of determination of friction angle of soil applying latterly developed double-punch test method. Sandy loam soil was taken as sample soil for the study. Some factors which may affect the double-punch test were also studied thoroughly. These factors include sample-punch size, punch diameter, moisture content etc. The formulation of punch equation is based on plasticity theory of the upper bound limit theorem. The calculation of soil strength and its related parameters require only the simple linear analysis. The study revealed that the friction angle of soil obtained for different moisture contents were realistic and the double punch test may be treated as the most useful technique of determining tensile strength of both rigid and loose materials.